ADI-DSP based software interface for rapid prototyping - Picasos, Patrick M. (2001)
The ADI-DSP based Software Interface for Rapid Prototyping is a tool for generating a prototype black box for any given transfer function H (s) and H (z), or an analog and digital filter design. The prototype is composed of the ADSP 2181 Development Board and the necessary assembly code running on it. With the use of a C-based screen interface, the user will have to input his design specifications and parameters, usually described by filter or transfer function coefficients, in s-domain (analog) or in z-domain (digital). After the user has provided the specifications together with his choice of design structure, the project will automatically generate the necessary Assembly Code defining the design. This is done through the use of pre-coded assembly text files that are manipulated and updated accordingly by the C-program. The project also handles the assembly and linking of the code using the provided assembler and linker. It has also the capability to download the generated object file to the provided ADSP 2181 Development Board using a serial port interface. With the necessary program running on board, the ADSP 2181 system functions as a prototype black box for the user-defined filter or transfer function design. The user can now use the board as part of a larger circuit design.